Motivations of everyday food choices - Phan Thuy, Xuan Uyen (Kansas State University, 2015)
Understanding “why people eat what they eat” is important for improving the lives of people around the world by helping provide industrial and social solutions for people so that they may have greater pleasure and health from the foods they choose. The objectives of the research were to investigate motivations behind everyday meals and choices of different food groups using three different approaches incorporating two psychological perspectives: top-down and bottom-up. The first approach was the Eating Motivation Survey (TEMS) targeting the specific choices of foods and beverages people consumed at specific eating events (breakfast, mid-morning snack, lunch, mid-afternoon snack, dinner, and late-night snack). The second approach was the Food Choice Map (FCM) technique to explore motivations for individual food choices for all eating within a typical week. These two approaches employed the bottom-up process. The last approach used TEMS to investigate food choice directly for six eating occasions, without information about what were eaten specifically. This procedure demonstrated a top-down process because people first thought about their eating as a whole and then read through all TEMS scales to find the motivations that they consider "appropriate" for their answers. The first surveys were completed by 198 participants. The FCM interview was conducted on 100 respondents and the same respondents also participated in the last approach. Data were analyzed by Correspondence Analysis. Liking was the strongest motivation that drove people’s food choice. In addition, need and hunger, habits, price, and convenience were the other main motivations for breakfast, lunch, and dinner while health and weight control were found to be the main driving factors for mid-morning and mid-afternoon snacking. Late-night snacks were linked to pleasure and visual appeal. For dinner, people also were motivated most by variety seeking and traditional eating. Different food groups were also chosen with different motivations. Grain, pasta, meats and poultry were linked to convenience, variety seeking, traditional eating, and price while nuts, seeds, eggs and dairy were associated with need and hunger, health, and weight control. Findings from this project advanced and reinforced the knowledge about food choice and encouraged investigating food choice from different perspectives.
Keywords: Food choice; Motivation; Dietary behavior; Eating motivation; Food Science (0359); Nutrition (0570)